Upregulation of the Chemokine Receptor CCR7 expression by HIF-1αand HIF-2α in non-small cell lung cancer - Yang LI (Chinese Journal of Lung Cancer, 2008)
Background and objective CCR7 is closely related with the lymph node metastasis of non-small cell lung cancer. The objective of this work is to investigate the expressions of chemokine receptor CCR7, hypoxiainducible factor 1α (HIF-1α) and hypoxia inducible factor 2α (HIF-2α) protein in non small cell lung cancer and the relationships of their expression, and to study the mechanism of CCR7 upregulation in NSCLC. Methods T he levels of expressions of CCR7, HIF-1α and HIF-2α protein were detected in 94 specimens of human primary non small cell lung cancer by immunohistochemical S-P method. Human lung adenocarcinoma cell line A549 cells were transfected by lipofection with HIF-1α siRNA、HIF-2α siRNA, the change of CCR7 was observed by RT-PCR and immunofluorescence staining. Correlations between the expression of CCR7 and HIF-1α, HIF-2α were respectively analyzed. Results Immunohistochemistry showed that CCR7 was distributed in cytoplasm and/or membrane of tumor cells, HIF-1α, HIF-2α was distributed in nucleus and/or cytoplasm of tumor cells. The levels of expressions of CCR7, HIF-1α and HIF-2α protein were found to be 75.53% (71/94), 54.25% (51/ 94) and 70.21% (66/94) in non small celllung cancer, respectively. the levels of expression of CCR7 protein were closely related to the clinical stages (P <0.001) and lymph node metastasis (P <0.001) of non small cell lung cancer, but there was no correlation with age, gender, histology (P >0.05). Furthermore, A significant correlation were found among CCR7, Hif-1α and HIF-2α (r =0.272, P <0.01) (r=0.225, P <0.05). In addition, the expression of CCR7 mRNA and protein levels were decreased in the transfected specificHIF-1α, HIF-2αsiRNA group (P <0.05). Conclusion CCR7 expression is significantly associated with non small cell lung cancer invasion and metastasis. The upregulation of CCR7 is regulated by HIF-1α and HIF-2α in non small cell lung cancer.